Pengaruh Kualitas Pelayanan, Fasilitas Kampus, Dan Citra Kampus Terhadap Kepuasan Mahasiswa Universitas Dharma Andalas - Fadila Salsabila Zalma; Maivalinda Maivalinda (CV. ITTC INDONESIA, 2025)
This study aims to determine the Quality of Service, Campus Facilities, and Campus Image on Student Satisfaction at Dharma Andalas University. The population in this study were active students of Dharma Andalas University in 2024, Faculty of Economics and Business, Faculty of Law, Social Sciences and Humanities, and Faculty of Science and Engineering, totaling 1,569 students. The sample in this study was 95 and the sampling was 100 respondents to avoid errors in filling out the questionnaire, with the characteristics of active students, namely students in 2024, class of 2022 to class of 2024. This research is a quantitative research. The instrument used in this study was a questionnaire. The results of the study using multiple linear regression analysis showed that simultaneously there was a significant influence of service quality, campus facilities, and campus image on student satisfaction at Dharma Andalas University.